Effect of fuel concentration on structural, vibrational, morphological properties and particle stability of NiO nanoparticles. Issue 24 (15th December 2022) - Praveenkumar, V.; Janarthanan, E.; Ranjith Kumar, E.; Ranjithkumar, B.; Sathiyaraj, S.; Ramalingam, H.B.; Alharthi, Salman S.
Abstract: In this present research, a simple cost-effective auto-combustion method has been adopted to prepare NiO nanoparticles with nickel nitrate and urea as raw materials. Urea has been taken as a fuel to perform combustion processes with different concentrations (50%, 75%, and 100%). The effects of urea concentration on structural, optical, morphological properties, and colloidal stability of NiO nanoparticles were analyzed through various techniques (XRD, FT-IR, SEM, and Zeta Potential analyzer). The single-phase cubic structure of NiO nanoparticles was examined through an XRD profile, and it confirms that the crystallite size of the nanoparticles is in the nanoscale range. The average crystallite size of NiO nanoparticles increases with an increase in fuel concentration (18.2 nm for 50%, 27.3 nm for 75, % and 38.4 nm for 100%). Among three different fuel ratios, 50% urea has been concluded as the optimum fuel ratio to prepare fewer particles. The functional groups present in all three samples were recorded by FT-IR spectra, which confirms the metallic Ni-O presence in all the samples. The role of fuel ratio on morphology was also examined by SEM micrographs, and morphological changes under three fuel ratios were also observed. The colloidal stability of NiO nanoparticles for all three samples was analyzed by a zeta potential analyzer, and it confirms that the stability of the samples is varied with fuel ratios. Using UV–vis spectra, the optical band gap of NiO nanoparticles was calculated. The optical band gap of NiO nanoparticles decreases as particle size increases.